Character Development Based on Hybrid Learning in the Post-Pandemic Era - Mirza Mahbub Wijaya; Mamdukh Budiman (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
Corona Virus Disease 19 is currently a global virus outbreak and impacts the order of life, including education. The Covid-19 virus pandemic, the lecture system or learning from conventional was shifted to super-high technology to innovate learning models, including the Hybrid Learning model. The innovation of the face-to-face learning model (PTM) Hybrid Learning is based on character aspects. This research method uses a qualitative descriptive-analytic method. The results of this study are lectures with the Hybrid Learning model with an Odd-Even model or scheme. The first meeting of students with an even attendance number attends offline lectures in class with a maximum number of specific provisions and uses the Health protocol tool. Meanwhile, students with odd attendance numbers attend lectures. Online virtual in their respective places and vice versa. There are character values that are integrated into the lecture model, such as learning tips. Conclusion, Overall, lectures with the Hybrid Learning model, both lecturers and students, have virtual interactive discussions and integrated character values in the lecture model, such as learning tips. For example, it is forbidden to cheat; everyone must be honest. For example, it is prohibited to cheat, be honest, be disciplined in time, cooperate in teams, and be responsible for the lecture process and the work assigned by lecturers to students